Peran Orang Tua Dalam Menstimulasi Moral Anak Usia (5-6) Tahun Saat Menggunakan Gadget Masa Pandemi Covid-19 Di Kelurahan Srijaya - Baqiyatur Rahma Sholeha; Sri Sumarni (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2023)
This study aims to describe how the role of parents in stimulating the kinesthetic intelligence of children aged 5-6 years during covid-19 in Mambang Musi Rawas Village. This study uses a qualitative descriptive research where the data collection techniques used in this research subject are interviews, observation, and documentation. Furthermore, to reduce the data that has been obtained in the field by taking the main and important data, make a categorization that presents the data in the form of a narrative text. In this study the researchers used two (2) parents of children aged (5-6) years old who was in Mambang Village at the time of covid-19. The results of this study were obtained, The role of parents in stimulating kinesthetic intelligence of children aged (5-6) years at the time of covid-19 in Mambang Village is the role of parents in stimulating kinesthetic intelligence as educators, protectors, motivators, facilitators, and mentors. As well as activities that can stimulate children's kinesthetic intelligence, namely: playing badminton and playing bicycles